Collagen--proteoglycan interactions. Localization of proteoglycans in tendon by electron microscopy. - Scott, J E (1980)
Proteoglycan in foetal- and adult-rat tail tendon and adult-rabbit achilles tendon was stained for electron microscopy with a cationic phthalocyanin-like dye, based on cinchomeronic acid, in a 'critical electrolyte concentration' method [Scott (1973) Biochem. Soc. Trans. 1, 787-806). Provided that the tissue was fixed with glutaraldehyde or formaldehyde, regular orthogonal perifibrillar arrays of filamentous material (proteoglycan) were observed, but no intra-fibrillar proteoglycan was seen. Specific proteoglycan-collagen interactions are inferred, and a model is proposed. Without fixation, the filamentous arrays disaggregated in the MgCl2 solutions (0.3 M) used during staining. End-to-end proteoglycan aggregation is implied. Tendon and cartilage are compared. Problems of electron-histochemical localization of extended space-filling polyanions by the use of cationic electron-dense precipitants are discussed, particularly polyanion-domain collapse, specificity of staining and fixation. A two-stage staining procedure that markedly enhances contrast is described, based on the multivalent nature of the dye, and the consequent anion-exchange properties of the dye-polyanion complex.